Highly precise Ti/Pt/Cr/Au thin-film temperature sensor embedded in a microfluidic device - Wang, Jie-Jun; Wang, Tao; Wu, Chuan-Gui; Luo, Wen-Bo; Shuai, Yao; Zhang, Wang-Li (Rare metals, 2021)
A multilayer (Ti/Pt/Cr/Au) resistive temperature sensor was proposed and investigated to precisely measure the temperature characteristic in microfluidic devices. The Ti/Pt/Cr/Au sensor was fabricated by direct current (DC) sputtering, vacuum evaporation and liftoff process. The thermal annealing test was conducted in the temperature range of 200–800 °C for obtaining an appropriate property of the multilayer. Based on the experimental results, 400 °C was selected as the experimental annealing temperature for the Ti/Pt/Cr/Au layer. The redistribution of structural imperfections and recrystallization promote the density and adhesion of multilayer during the annealing process. With the annealing temperature rising, the annealing process leads to through-thickness migration of chromium and partial depletion of the adhesive layer. The Ti also diffuses into the Pt, which makes the interface disappear. Nevertheless, the layer remains continuous. The temperature coefficient of resistance (TCR) of the sensors was investigated through the microfluidic testing system. The excellent stability and sensitivity of the Ti/Pt/Cr/Au thin-film temperature sensor are verified. Furthermore, the capability of the Ti/Pt/Cr/Au thin-film temperature sensor detecting the sudden temperature change caused by bubble effect is very meaningful to the microfluidic devices.